Polymeric nanocomposite-based herbicide of carboxymethyl cellulose coated-zinc/aluminium layered double hydroxide-quinclorac: a controlled release purpose for agrochemicals - Norhayati Hashim (Tanjung Malim, 2021)
Polymeric nanocomposite-based herbicide of carboxymethyl cellulose coated-zinc/aluminium layered double hydroxide-quinclorac: a controlled release purpose for agrochemicals by Norhayati Hashim